Improving Children’s Reading Motivation and Skills Through Read Aloud: A Mixed-Method Study in Orphanage Context - Wahyuningsih, Effi; Suciyati, Nunung; Rahman, Danis Fatika (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2023)
Generally speaking, children's reading motivation and skills are low, notably those in orphanages requiring solution, one of which is through reading activities applying read-aloud method. Most studies on the read-aloud method were qualitative. This study attempted to address the gap by employing a mixed-methods design with 10 foster children from an orphanage chosen using purposive sampling technique. Observations, tests, and interviews were used to collect the data. Quantitative data from observations and tests were statistically analyzed and reported in frequency and percentage to determine the difference in the number of children who improved following the program. Additionally, interviews were conducted to obtain qualitative data on children's and orphanages' perspectives of the program and its impacts, and the results were assessed using qualitative data analysis including data reduction, data display, and conclusion drawing. Both quantitative and qualitative data were gathered and analyzed concurrently. They were then merged and interpreted through a side-by-side comparison approach. Finally, convergence or divergence between the two sources of data was determined. The findings show that quantitative and qualitative data confirm each other, demonstrating that the read-aloud method improved children's reading motivation by significantly increasing the length of time for reading and the number of books read, as well as a slight increase in children's reading comprehension and confidence. In addition, the children's reading fluency improved substantially, while their reading accuracy and clarity improved slightly. Future research should focus on areas that need the most improvement and entail a larger sample size. Additionally, reading assistance for foster children is always recommended.